Could the R-Ratio Be an Indicator of Acute Liver Injury for the Treatment of COVID-19 - Kayacan, Yıldırım; Yazar, Hayrullah; Özdin, Mehmet; Kayacan, Yildrim; Yazar, Hayrullah; Ozdin, Mehmet (Istanbul Univ, Fac Medicine, Publ off, 2021)
Objective: The aim of the study was to determine whether the R-ratio could be an indicator in COVID-19 patients. Material and Method: Alkaline phosphatase (ALP) and alanine aminotransferase (ALT) were measured in the first blood serum of all patients (n=314), and R-values were determined and grouped. Then, the correlations between the detected parameters were examined and the differences were analyzed by gender. Patients were compared according to the ALT and ALP upper values of the reference interval. Alpha value was accepted as <0.05. Results: In all patients, ALT and ALP were detected well above normal reference ranges (p=0.000). The R-value ratio was significantly associated with ALT and ALP (p<0.001). R-groups were statistically significant and inversely proportional to age (p=0.049). It was detected that the R-ratio of >= 5 was higher in women than in men. Conclusion: According to our findings, ALT and ALP measurements in patients diagnosed with COVID-19 were much higher than normal. Another interesting result of our research was that the R-ratio was found to be <= 2 in the majority of our patients. The R <= 2 finding, which is accepted as an indicator of acute liver injury, suggested that tracking of this value for COVID-19 could be an important indicator.
R-Oranı, Covid-19 Tedavisinde Akut Karaciğer Hasarının Bir Göstergesi Olabilir mi?
ESCI
Kayacan, Yildirim/0000-0003-2784-2980;
Keywords: SARS-CoV-2; COVID-19; R-Ratio; ALT; ALP; Medicine